(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
There is described a method of generation the rigid feature “Force – Settlement” for thin- layer rubber-metal compensating elements, which consist of several rubber and non-elastomeric layers, operating when being pressed, taking into account the low compressibility of rubber layers and deformation of support non-elastomeric layers. Variational method of theory of elasticity for compressible materials is used. It is recommended to use the acquired analytic dependencies when analysing the element and designing multi- layer compensating elements, as well as when determining the value of Poisson coefficient for rubber-like materials.